Problematizações sobre o ensino multisseriado: olhares sobre a escola do campo Presidente Artur da Costa e Silva em Concórdia do Pará - SILVA, Tassia Gonçalves da (2023)
This scientific article is intended for course completion purposes, addressing the theme of rural education, with emphasis on the multiseriate classes that are predominant in schools in rural areas, with an emphasis on locations in the Amazon in the state of Pará, bringing my memories of former student from the Escola Presidente Arthur da Costa e Silva. The study aims to discuss about Rural Education and the struggles of social movements for better living conditions and for the reaffirmation of public educational policies that value the rural individual within their particularities, and seeks to discuss the precariousness of teaching in rural areas in multiseriate classes. The research is of the bibliographic and autobiographical type and brings a qualitative approach, with theoretical basis in the studies of authors such as Hage, Caldart, Moraes, Barros and Côrrea. Finishing of the study, it can be seen that the problems faced by educators and students in rural schools are still far from over and that the struggle for the right to receive a quality education in the experience space of rural actors needs to be constant.